High frequency of H3 K27M mutations in adult midline gliomas - Ebrahimi, Azadeh; Reuss, David (Journal of cancer research and clinical oncology, 2019)
PurposeDiffuse midline gliomas, H3 K27M-mutant were introduced as a new grade IV entity in WHO classification of tumors 2016. These tumors occur often in pediatric patients and show an adverse prognosis with a median survival less than a year. Most of the studies on these tumors, previously known as pediatric diffuse intrinsic pontine glioma, are on pediatric patients and its significance in adult patients is likely underestimated.MethodsWe studied 165 cases of brain tumors of midline localization initially diagnosed as diffuse astrocytomas, oligodendrogliomas, pilocytic astrocytomas, supependymomas, ependymomas and medulloblastomas in patients with an age range of 2-85.ResultsWe identified 41 diffuse midline gliomas according WHO 2016, including 12 pediatric and 29 adult cases, among them two cases with histological features of low grade tumors: pilocytic astrocytoma and subependymoma. 49% (20/41) of the patients were above 30 years old by the first tumor manifestation including 29% (11/41) above 54 that signifies a broader age spectrum as previously reported. Our study confirms that H3 K27M mutations are associated with a poorer prognosis in pediatric patients compared to wild-type tumors, while in adult patients these mutations do not influence the survival significantly. The pattern of tumor growth was different in pediatric compared to adult patients; a diffuse growth along the brain axis was more evident in adult compared to pediatric patients (24% vs. 15%).ConclusionH3 K27M mutations are frequent in adult midline gliomas and have a prognostic role similar to H3 K27M wild-type high-grade tumors.
Gesehen am 15.05.2019
Published online: 4 January 2019